Effectiveness of the Breastfeeding Self-efficacy and Family Support Enhancement Program among First-time Postpartum Mothers: A Randomized Controlled Trial - Chainakin, Pattiya; Sansiriphun, Nantaporn; Chaloumsuk, Nonglak; Deeluea, Jirawan (Pacific Rim International Journal of Nursing Research, 2023)
First-time mothers often lack effective breastfeeding techniques and may perceive they have insufficient milk due to inadequate experience in breastfeeding. There are limited programs for enhancing effective breastfeeding and perceived sufficient milk among first-time mothers in Thailand. This randomized controlled trial study investigated the effects of the Breastfeeding Self-Efficacy and Family Support Enhancement Program on effective breastfeeding and perceived sufficient milk among first-time mothers. The participants included 64 pairs of first-time mothers with normal labor and their family members. They were recruited from an antenatal clinic in a province of Thailand and randomly assigned to the experimental arm (n = 32) to receive the program in addition to standard care or the control arm (n = 32) to receive only standard care. Data were collected using the Demographic and Obstetric Data Questionnaires, the Bristol Breastfeeding Assessment Tool, H&H Lactation Scale for first-time mothers, and a demographic data questionnaire for family members. Data analysis was performed with descriptive statistics, Chi-square test, and two-way mixed ANOVA. The results indicated that, after receiving the program, the mean scores on effective breastfeeding and perceived sufficient milk at days 3, 10, and 28 postpartum in the experiment group were significantly higher than before receiving the program and significantly higher than that of the control group. Nurses can integrate this program to train family members to support first-time mothers in breastfeeding continuously and increase first-time mothers’ confidence in their ability to breastfeed effectively and perceive milk sufficiency. However, further testing of the program effectiveness is warranted.